ENGAGING MOBILE ASSISTED LANGUAGE LEARNING (MALL) INTO EFL LISTENING CLASS - Iwan Ridwan (JUDIKA (JURNAL PENDIDIKAN UNSIKA), 2019)
The objective of this research was to find out the progress of the students’ listening fluency through Mobile Assisted Language Learning (MALL). The researcher used Classroom Action Research with twenty four samples at Senior High School or SMA Muhammadiyah Karawang who have experienced using Mobile Phone in any applications needed. To make the teaching-learning process clear and relevant should be supported by the experts’ theories, such as Howatt and Dakin (1974) stated that Listening is the ability to identify and understand what other saying. It is also supported by Howard Gardner (1983) by saying that Teachers have begun to understand how using audio in the classroom can increase the circle of readers by engaging learners with auditory and spatial intelligence learning style. Moreover, mobile phone is a portable device that can be brought anywhere and anytime we want to. Despite there is no agreement about defining Mobile Assisted Language Learning (MALL), (Traxler?s, 2005) defined mobile learning as any educational provision where the dominant technologies are handheld devices. Also, (O?Malley et al., 2003: 6) defined mobile learning as a type of learning that takes place when the learner is not at a fixed location, or when the learner takes advantage of the learning opportunities offered by mobile technologies. This study showed that MALL improved the students’ listening skill. Therefore, the researcher suggested that EFL teachers use Mobile Assisted Language Learning as an alternative way to improve students’ listening skill and teaching quality as well.